External complexation of BODIPYs by CB[7] improves in-cell fluorescence imaging - Ayhan, Mehmet Menaf; Ozcan, Emrah; Alkan, Fahri; Cetin, Metin; Un, Ilker; Bardelang, David; Cosut, Bonyemin (Royal Soc Chemistry, 2022)
Organic luminescent compounds with high emission properties play a crucial role in fluorescence labelling and optoelectronic devices. In this work, we prepared three water soluble BODIPY derivatives (B-4, B-5, and B-6) which are weakly fluorescent due to non-radiative relaxation pathways (charge transfer: CT or heavy atom effect). However, CB[7] significantly improves BODIPY fluorescence by similar to 10 fold for B-4, and by similar to 3 fold for B-5. The (TD)DFT analyses suggest that for B-4 and B-5, the CT state is blue-shifted as a result of the external binding of CB[7] near the pyridinium groups. This effect favoured a radiative decay through a locally-excited (LE) pi ->pi* transition state of BODIPYs resulting in a CB[7]-induced emission increase in solution (and in the solid state), without compromising singlet-to-triplet intersystem crossing (ISC). The improved emission of the BODIPY center dot CB[7] complexes was used for the fluorescence imaging of U87 cells illustrating the relevance of this approach. These results suggest that BODIPY center dot CB[7] complexes could be used as theragnostic agents by combining fluorescence imaging and treatment by photodynamic therapy.
Keywords: Solid-State; Enhanced Fluorescence; Dyes; Photosensitizers; Derivatives; Emission; Macrocycles; Binding; Design